Front Matter - Jalan Jembatan, Jurnal (Jurnal Jalan Jembatan, 2024)
This section contains the cover, table of contents, preface, and a collection of abstracts from Volume 41, No. 1 January-June 2024 and Volume 41, No. 2 July-December 2024.